Opinions and Practice of US-Based Obstetrician-Gynecologists regarding Vitamin D Screening and Supplementation of Pregnant Women - Sara A. Mohamed; Ayman Al-Hendy; Jay Schulkin; Michael L. Power (Journal of Pregnancy)
Vitamin D deficiency/insufficiency is prevalent among pregnant women. Recommendations for adequate levels of circulating 25-hydroxyvitamin D and appropriate vitamin D supplementation during pregnancy differ between the Institute of Medicine and the Endocrine Society. Obstetrician-gynecologists must make clinical decisions in this environment of uncertain guidance. An online questionnaire regarding physician practice patterns for screening and supplementing pregnant women was administered to 225 randomly selected practicing obstetrician-gynecologists of whom 101 (45%) completed the questionnaire. A majority indicated that vitamin D insufficiency was a problem in their patient population (68.4%) and that most of their pregnant patients would benefit from vitamin D supplementation (66.3%). Half (52.5%) would recommend vitamin D supplementation during pregnancy to some patients, but only 16.8% to all. Only one in four (25.8%) routinely screen their pregnant patients for vitamin D status. Physicians who indicated that vitamin D status was a problem in their patient population were more likely to screen routinely (32.8% versus 9.7%, P=0.002) and believe their patients would benefit from supplementation (91.2% versus 16.1%, P=0.001). Opinion regarding supplementation levels and indicators of adequacy were split between the two competing recommendations, suggesting that clinical practice will likely remain variable across physicians, with uncertain public health consequences.